The Relationship between the Organizational Justice and Organizational Citizenship Behavior among Medical Records Staffs of Selected - Maryam Yaghoubi (مدیریت اطلاعات سلامت, 2011)
Introduction: Organizational justice is a variable that predicts many organizational variables. One of these variables that have an important role in many organizations today is organizational citizenship behavior. So this study aimed to study the relationship between organizational justice and organizational citizenship behavior among medical record staff in selected hospitals of Isfahan in 2008. Methods: In this descriptive correlation study, medical record stuffs were included. Data collected using two questionnaires:  organizational justice, and organizational citizenship behavior questionnaire. The questionnaires reliability was supported based on Cronbach Alfa .and questionnaire validity confirmed by specialist view of point. Data analyzed by SPSS software. Results: Mean score of organizational justice among hospital stuff in Isfahan was 40.9+/-18.1.between hospitals in Isfahan. The highest and lowest score was related to distributive and interactive justice, respectively. There was no significant relationship between organizational justice and conscientiousness, altruism, sportsmanship. There was a significant  relationship between organizational justice and civic virtue, courtesy and organizational citizenship behavior (P<0.001). Conclusion: Since the score of organizational citizenship behavior and organizational justice among stuff of selected hospitals were moderate and the score of interaction justices was weak. Therefore, hospital managers should provide the backgrounds of creating and improvement of perceived justice among staff. Keywords: Organizations; Behavior; Medical Records; Variables.